Solution-Mediated Modulation of Pseudomonas aeruginosa Biofilm Formation by a Cationic Synthetic Polymer - Leanna L. Foster; Shin-ichi Yusa; Kenichi Kuroda (MDPI AG, 2019)
Bacterial biofilms and their associated infections are a continuing problem in the healthcare community. Previous approaches utilizing anti-biofilm coatings suffer from short lifetimes, and their applications are limited to surfaces. In this research, we explored a new approach to biofilm prevention based on the hypothesis that changing planktonic bacteria behavior to result in sub-optimal biofilm formation. The behavior of planktonic Pseudomonas aeruginosa exposed to a cationic polymer was characterized for changes in growth behavior and aggregation behavior, and linked to resulting P. aeruginosa biofilm formation, biomass, viability, and metabolic activity. The incubation of P. aeruginosa planktonic bacteria with a cationic polymer resulted in the aggregation of planktonic bacteria, and a reduction in biofilm development. We propose that cationic polymers may sequester planktonic bacteria away from surfaces, thereby preventing their attachment and suppressing biofilm formation.